2017
DOI: 10.1002/ps.4726
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between gut microbiota and entomopathogenic fungi: a potential approach for biological control of Blattella germanica (L.)

Abstract: The gut microbiota of German cockroaches may play a critical role in protecting cockroaches from fungal invasion and colonization. Removing certain bacteria from the B. germanica microbiota may facilitate microbial control using fungal pathogens. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…There were, however, also potentially pathogenic species, especially associated with A. major and E. similis . Recent advances in studying insect–microbe interactions have shown that entomopathogens play an important role in insect pest biocontrol . For example, Bacillus thuringiensis (Bt) toxins that are widely used in sprays and transgenic crops have proven useful in controlling insect pests .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were, however, also potentially pathogenic species, especially associated with A. major and E. similis . Recent advances in studying insect–microbe interactions have shown that entomopathogens play an important role in insect pest biocontrol . For example, Bacillus thuringiensis (Bt) toxins that are widely used in sprays and transgenic crops have proven useful in controlling insect pests .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in studying insect-microbe interactions have shown that entomopathogens play an important role in insect pest biocontrol. 67 For example, Bacillus thuringiensis (Bt) toxins that are widely used in sprays and transgenic crops have proven useful in controlling insect pests. 68 Similarly, bacteria of the Pseudomonas protegens species are capable of invading and killing agriculturally important plant 71 pest insects, such as the cabbage butterfly Pieris brassicae (Lepidoptera: Pieridae), which makes them promising candidates for biocontrol applications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future research is needed to determine whether these dominant midgut microbial species can degrade the key components of potato leaves and tubers. In addition, some studies have shown that gut microbiota can mediate resistance to chemical insecticide [14][15][16], while others have shown that entomopathogenic fungi interacts with the gut microbiota to accelerate pest mortality [36][37][38]. So, different gut microbiota leaf-feeding Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One-way ANOVA and Duncan's (α = 0.05) test were used to compare the microbial diversity and abundance at the phylum level using SPSS 22.0 (IBM Corporation, New York, United States) [53]. A Venn diagram was prepared with R software [54], while non-metric multidimensional scaling (NMDS) based on the Bray-Curtis algorithm and figures were prepared with the Vegan package [55,56]. Variations of species among groups at the genus level were examined with the Kruskal-Wallis test.…”
Section: Discussionmentioning
confidence: 99%